Urban Expansion and Real Estate Dynamics: Comparing Real Estate Agent Land Strategies in medium-sized cities - Bruno Leonardo Silva Barcella (Sociedade & Natureza, 2020)
This article analyzes the recent urban territorial expansion in two medium-sized Brazilian cities (Ribeirão Preto/SP and São Carlos/SP) and discusses the close relationship between the interests and strategies of specific real estate and land agents and the selective direction, rhythm, scope, and magnitude of the cities’ expansion. To this end, data on land transactions (purchase and sale) between 1995 and 2015, are mapped for both cities, showing the prices, information on the production of gated communities, and the main agents involved. Their permanent quest to amplify the reproduction of capital is the backdrop for the debate, through a logic that places the city as the "locus" of the accumulation strategies. This is articulated in the economic dimension by the transformation of land income into incorporated profits and spatially by the differentiated, exclusive housing.